Effects of microbial fertilizers on tobacco plants and soil microbial community during the prosperously growing stage - Guo, Chunsheng; Hao, Jie; Ma, Shangyi; Hong, Jie; Wang, Shengli; Zhang, Lei; Zhang, Bao; Ding, Hai; Liu, Xingming; Xing, Shuo; Sun, Jian; Shen, Guoming; et al. (Frontiers in Soil Science, 2025)
IntroductionTobacco, as an important economic crop, shows significant growth and yield responses to soil conditions and nutrient supply. In recent years, microbial organic fertilizers (MOF) have garnered significant attention as a novel fertilizer category due to their demonstrated potential for soil quality improvement and plant growth promotion. This study aims to evaluate the effects of MOF on tobacco growth in Hunan Province, with particular focus on its long-term impacts on soil physicochemical properties and rhizosphere microbial communities throughout the tobacco growth cycle. MethodsWe evaluated the effects of T1 (Basic fertilizer + Bacillus), T2 (Basic fertilizer + Pseudomonas), and T3 (Basic fertilizer + Bacillus and Pseudomonas) treatments on tobacco quality, soil parameters, and microbial communities. Soil physicochemical properties were measured using standardized analytical methods. Microbial community dynamics under different treatments were analyzed via 16S rRNA sequencing and PICRUSt2 analysis. Results and DiscussionThe results indicate that microbial fertilizers can significantly enhance soil fertility and promote tobacco growth by modulating soil microbial communities. Specifically, the T1 organic fertilizer treatment demonstrated the most pronounced effect in reducing microbial abundance, as evidenced by a lower Sobs value of 4, 222 compared to 4, 825 in the control group (p < 0.05). Furthermore, this treatment significantly enhanced the visual quality of tobacco leaves. This study provides a scientific foundation for the application of microbial fertilizers in tobacco cultivation and offers new perspectives for sustainable agricultural development.